2020
DOI: 10.1016/j.abrep.2020.100323
|View full text |Cite
|
Sign up to set email alerts
|

Component process analysis of verbal memory in a sample of students with a binge drinking pattern

Abstract: Highlights Student binge drinkers have reduced performance on learning a 24-word list. This is due to low proficiency in encoding, storage and retrieval processes. Memory processes are impacted by consumption speed and intoxication episodes. Academic failure described among binge drinkers could be partly related to findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
1
10
0
2
Order By: Relevance
“…Finally, the remaining investigators in this Special Issue explore binge drinking-related consequences through neuropsychological assessments. Examining memory processes, Gierski et al (2020) show impaired storage and recollection processes in verbal episodic memory, although no evidence was found for difficulties in verbal working memory. This finding clearly indicates that binge drinking should not be considered a recreational pattern and could shed light on how short-term binge drinking already affects academic performance ( Kuntsche et al, 2017 , Páramo et al, 2020 , Patte et al, 2017 ).…”
Section: Summary Of the Current Special Issuementioning
confidence: 77%
See 1 more Smart Citation
“…Finally, the remaining investigators in this Special Issue explore binge drinking-related consequences through neuropsychological assessments. Examining memory processes, Gierski et al (2020) show impaired storage and recollection processes in verbal episodic memory, although no evidence was found for difficulties in verbal working memory. This finding clearly indicates that binge drinking should not be considered a recreational pattern and could shed light on how short-term binge drinking already affects academic performance ( Kuntsche et al, 2017 , Páramo et al, 2020 , Patte et al, 2017 ).…”
Section: Summary Of the Current Special Issuementioning
confidence: 77%
“…This Special Issue gathers 11 original research and review articles that address different types of binge behaviors: binge drinking ( Deniel et al, 2021 , Gierski et al, 2020 , Herman et al, 2020 , Mange et al, 2021 , Werle et al, 2021 ), binge eating ( Prunell-Castañé et al, 2021 , Werle et al, 2021 ), binge watching ( Cordeiro et al, 2021 , Ort et al, 2021 , Rubenking and Bracken, 2021 , Werle et al, 2021 ), and binge-porn consumption (i.e., hypersexuality and problematic pornography use; Castro-Calvo et al, 2021 , Koós et al, 2021 ). These articles primarily consist of empirical studies that build on self-report questionnaires, but a few rely on behavioral assessments, ecological approaches (i.e., sampling experiences), or literature reviews.…”
Section: Summary Of the Current Special Issuementioning
confidence: 99%
“…Authors and scholars found that student-drinkers obtained a low scholastic performance (El Ansari et al, 2013;Conegundes et al, 2020;Dumbili, 2020;Frederick, 2020). Gierski et al (2020) discovered that binge drinking is perhaps partly related to academic failure. Meanwhile, Nyandu and Ross (2020) reported a high proportion (78%) of not performing poorly on a test examination despite their alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the most salience of the study, the high -risk and problem drinkers become the topmost priorities to assess and have preferential investigation by the school to address the prevalence, behaviors, factors, and other mitigating conditions (Allen et al, 2020;Dumbili, 2020;El Ansari et al, 2020;Gierski et al, 2020;Granja et al, 2020;Kazemi et al, 2020;Hahn et al, 2020;Hernandez et al, 2020;Oluwafemi, 2020;Rose et al, 2020;Smith, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indo além da concepção categórica de consumo excessivo de álcool, foi possível identificar que os níveis de eficiência desses processos de memória foram sistematicamente associados ao número de episódios de intoxicação nos 6 meses anteriores, destacando a natureza particularmente prejudicial da intoxicação repetida de álcool para processos de memória. No entanto, é possível a existência de um impacto diferencial, uma vez que a memória de trabalho verbal não foi afetada, enquanto a memória episódica verbal foi afetada (Gierski, 2020).…”
Section: Relação Entre O Consumo Excessivo De Bebidas Alcoólicas E a ...unclassified